2019
DOI: 10.1186/s12885-019-6090-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of neuroblastoma cells to RF currents as a function of the signal frequency

Abstract: Background Capacitive-resistive electric transfer (CRET) is a non-invasive therapeutic strategy that applies radiofrequency electric currents within the 400–600 kHz range to tissue repair and regeneration. Previous studies by our group have shown that 48 h of intermittent exposure to a 570 kHz CRET signal at a subthermal density of 50 μA/mm 2 causes significant changes in the expression and activation of cell cycle control proteins, leading to cycle arrest in human cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…In sum, the results of this study, which are consistent with previously reported collagenogenic and cytoproliferative effects of electric stimulation with the nonmodulated CRET signal (Hernández-Bule et al 2019, 2017, reveal that subthermal CRET stimulation is also effective in promoting fibroblast proliferation, the modulated signal being more effective than the nonmodulated one in eliciting such response. Furthermore, although in the short term (4 h:10 min) both signals induce significant overexpression of the collagen-specific chaperone Hsp47, only the modulated signal induces significant activation and overexpression of Hsp27 in the same early phase, as well as decorin overexpression 20 hours later (24 hours after the exposure onset).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In sum, the results of this study, which are consistent with previously reported collagenogenic and cytoproliferative effects of electric stimulation with the nonmodulated CRET signal (Hernández-Bule et al 2019, 2017, reveal that subthermal CRET stimulation is also effective in promoting fibroblast proliferation, the modulated signal being more effective than the nonmodulated one in eliciting such response. Furthermore, although in the short term (4 h:10 min) both signals induce significant overexpression of the collagen-specific chaperone Hsp47, only the modulated signal induces significant activation and overexpression of Hsp27 in the same early phase, as well as decorin overexpression 20 hours later (24 hours after the exposure onset).…”
Section: Discussionsupporting
confidence: 92%
“…We have also reported that, as is the case for other RF electric and magnetic fields, the cellular response to CRET currents is non-linearly dependent on the frequency of the sinusoidal signal (Hernández-Bule et al 2019). The modulation of the carrier signal is another parameter that has been shown relevant, both in the bioeffects induced by RF electromagnetic fields (Barbault et al 2009;Blackman 2012;Juutilainen et al 2011) as in those elicited by RF electric currents such as those used by the electric scalpel when in modes cutting vs. coagulation (Karaki et al 2019).…”
Section: Introductionmentioning
confidence: 65%
“…Subthermal CRET treatments can also exert anti-proliferative and/or cytotoxic effects in neuroblastoma and HCC cell lines through altering the expression of proteins involved in the MAPK/ERK1/2 signaling pathway ( 11 , 21 ). This pathway, when inhibited by sorafenib, restrains cell proliferation and induces apoptosis in HCC cells ( 17 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our previous studies have revealed that electrical currents used in CRET therapies, when applied in vitro at subthermal densities, could induce significant effects on the proliferation ( 8 ), differentiation ( 9 , 10 ) or viability of different human cell types ( 1 ). These effects, which differ between distinct cell types and are non-linearly dependent on RF signaling parameters, such as frequency, modulation or current density, were found to be mediated by electrically-induced changes in the regulation of proteins involved in the aforementioned processes ( 11 , 12 ). In cancer cells, CRET currents have been shown to induce anti-proliferative and/or cytotoxic responses ( 11 , 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation